Mechanistic Studies on the Epoxidation of Alkenes by Macrocyclic Manganese Porphyrin Catalysts. Issue 35 (24th May 2022) - Chen, Xiaofei; Duez, Quentin; Tripodi, Guilherme L.; Gilissen, Pieter J.; Piperoudis, Dimitrios; Tinnemans, Paul; Elemans, Johannes A. A. W.; Roithová, Jana; Nolte, Roeland J. M.
Abstract: Macrocyclic metal porphyrin complexes can act as shape‐selective catalysts mimicking the action of enzymes. To achieve enzyme‐like reactivity, a mechanistic understanding of the reaction at the molecular level is needed. We report a mechanistic study of alkene epoxidation by the oxidant iodosylbenzene, mediated by an achiral and a chiral manganese(V)oxo porphyrin cage complex. Both complexes convert a great variety of alkenes into epoxides in yields varying between 20–88 %. We monitored the process of the formation of the manganese(V)oxo complexes by oxygen transfer from iodosylbenzene to manganese(III) complexes and their reactivity by ion mobility mass spectrometry. The results show that in the case of the achiral cage complex the initial iodosylbenzene adduct is formed on the inside of the cage and in the case of the chiral one on the outside of the cage. Its decomposition leads to a manganese complex with the oxo ligand on either the inside or outside of the cage. These experimental results are confirmed by DFT calculations. The oxo ligand on the outside of the cage reacts faster with a substrate molecule than the oxo ligand on the inside. The results indicate how the catalytic activity of the macrocyclic porphyrin complex can be tuned and explain why the chiral porphyrin complex does not catalyze the enantioselective epoxidation of alkenes. Abstract : Ion mobility mass spectrometry reveals that a manganese (III) porphyrin cage reacts with the oxidant iodosylbenzene to form an inside iodosylbenzene complex, which is converted into a manganese(V)oxo complex in which the oxo group is located inside the cage (left). It reacts within the cage with alkenes to form epoxides. When the cage is blocked by methyl groups the reaction with iodosylbenzene and the formation of the manganese(V)oxo complex occurs at the outside of the cage (right). Subsequent reaction with alkenes takes place at the outside.